Manajemen Sarana dan Prasarana dalam Meningkatkan Kualitas Layanan Pembelajaran di SMAN 1 Lingsar - Susanti, Baiq Yuli; Hardiansyah, Hardiansyah; Iqbal, Muhammad (Universitas Pendidikan Mandalika, 2024)
Abstract: This study aims to examine the management of facilities and infrastructure and supporting factors for the quality of learning services. Optimal management of facilities and infrastructure will affect the quality of learning services and the availability of adequate facilities so that student satisfaction increases. The method used in this study is a qualitative method, with a type of qualitative descriptive research with a case study approach. Data collection techniques are carried out using interviews, documentation, and observation methods. Data analysis techniques through data collection, data presentation, data condensation, and conclusions. Data sources are obtained through the principal, head of administration, vice principal of infrastructure, teachers, and students. The results of this study indicate that: (1) management of facilities and infrastructure at SMAN 1 Lingsar is carried out through planning, organizing, implementing, and controlling, and the laboratory at SMAN 1 Lingsar has complete practical tools so that students can learn effectively (2) the quality of learning services at SMAN 1 Lingsar is quite effective in terms of the completeness of facilities and infrastructure in supporting learning (3) the role of facilities and infrastructure management in improving the quality of learning services at SMAN 1 Lingsar plays an important role in various management of learning facilities and infrastructure.Key Words: Management of Facilities and Infrastructure, Learning QualityAbstrak: Penelitian ini bertujuan untuk mengkaji pengelolaan sarana dan prasarana serta faktor-faktor pendukung kualitas layanan pembelajaran. Pengelolaan sarana dan prasarana yang optimal akan mempengaruhi kualitas layanan pembelajaran dan ketersediaan fasilitas yang memadai sehingga kepuasan mahasiswa meningkat. Metode yang digunakan dalam penelitian ini adalah metode kualitatif, dengan jenis penelitian deskriptif kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan dengan metode wawancara, dokumentasi dan observasi. Teknik analisis data melalui pengumpulan data, penyajian data, kondensasi data dan kesimpulan. Sumber data diperoleh melalui kepala sekolah, kepala administrasi, waka sarpras, guru dan siswa. Hasil penelitian ini menunjukkan bahwa: (1) pengelolaan sarana dan prasarana di SMAN 1 Lingsar dilakukan dengan perencanaan, pengorganisasian, pelaksanaan dan pengendalian serta laboratorium di SMAN 1 Lingsar yang memiliki kelengkapan alat praktikum sehingga siswa dapat belajar secara efektif (2) kualitas layanan pembelajaran di SMAN 1 Lingsar cukup efektif dalam hal kelengkapan sarana dan prasarana dalam menunjang pembelajaran (3) peran fasilitas dan pengelolaan infrastruktur dalam meningkatkan kualitas layanan pembelajaran di SMAN 1 Lingsar berperan penting dalam berbagai pengelolaan sarana dan prasarana pembelajaran.Kata Kunci: Manajemen sarana dan prasarana, Kualitas pembelajaranÂ